Analysis of the Role of Financial Literacy and Financial Inclusion on the Financial Performance of MSMEs - Wisudawaty, Ika; Nur Arisah (Cita konsultindo, 2025)
This study aims to comprehensively analyze the role of financial literacy and financial inclusion on the financial performance of MSMEs in Indonesia through a literature review from various reputable national and international sources. The results show that good financial literacy encourages MSMEs to make more informed financial decisions, improve the quality of financial reports, and strengthen risk management capabilities. Meanwhile, financial inclusion expands MSMEs' access to capital, insurance, and digital payment services, thereby increasing business efficiency and competitiveness. However, challenges remain, particularly in the 3T (frontier and remote) regions, such as disparities in access, limited infrastructure, and a dominant cash transaction culture. Therefore, integrated policy interventions are needed in the form of contextual financial literacy education, strengthening the digital financial ecosystem, and improving infrastructure. This study is expected to serve as a reference for researchers, practitioners, and policymakers in formulating sustainable MSME empowerment strategies in the digital era